Patient satisfaction in basic dental care clinic - Rosell, Fernanda Lopez [UNESP] (2024)
The interaction between dental students and patients is essential for practical and realistic learning, providing community services, and establishing a dental school clinic. Simultaneously, studies on public healthcare user satisfaction are crucial, contributing to corrective measures planning based on obtained information. The study aimed to understand the demographic and economic profile of patients treated at the Basic Dental Care Clinic of a public university and to assess patient satisfaction with the services and infrastructure. A cross-sectional observational study was conducted, collecting socioeconomic and general health data from patients through dental anamnesis. Validated questionnaires were used: Questionnaire for User Satisfaction with Public Oral Health Services, covering seven quality dimensions, and the Pompeu Questionnaire, addressing dental care aspects. Responses were tabulated for descriptive statistical analysis. Results: Questionnaire for User Satisfaction with Public Oral Health Services results indicate high patient satisfaction in various dimensions, such as human relations, treatment effectiveness, accessibility, and technical-scientific quality. The Pompeu Questionnaire reinforces these findings, emphasizing the students’ and professors’ receptiveness, effective guidance on oral care, and a high clinic recommendation rate by patients. In summary, both questionnaires reveal an overall positive patient satisfaction. In the study’s context, the majority of patients treated in the mentioned clinic expressed satisfaction with the physical structure, service, and dental treatment offered.